Peningkatan Kualitas Pembelajaran Berbasis Pendidikan Karakter di Pondok Pesantren Modern - Mudijono, Mudijono; Subando, Joko (Lembaga Yasin AlSys, 2025)
The quality of learning in modern Islamic boarding schools (pondok pesantren) is a critical issue in responding to the challenges of 21st-century education, which demands the integration of academic achievement and character development. This study aims to analyze the integration of character education within the learning process and its contribution to improving the quality of education in modern pesantren environments. A qualitative approach was employed using a case study design, with data collected through in-depth interviews, participatory observation, and documentation involving caregivers, teachers, and students (santri). The findings reveal that learning strategies based on role modeling, habitual practice, and the integration of character values into all subjects have a positive impact on students’ learning motivation, discipline, and active engagement. The study concludes that the comprehensive and consistent implementation of character education significantly enhances learning quality. The implications of these findings underscore the importance of teacher training, the strengthening of character-based management, and the development of a learning environment that supports the internalization of Islamic values within modern pesantren education.